PRODUKSI KOKON DAN BIOMASSA CACING TANAH Eisenia foetida PADA BERBAGAI MEDIA BUDIDAYA LIMBAH PETERNAKAN - Mashur Mashur (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2020)
Livestock waste has a major influence on environmental pollution, if not managed properly, because it will cause a foul odor. Efforts to manage livestock waste have not been successfully carried out completely, so new innovations are needed by utilizing the Eisenia foetida as a reactor to process it into earthworm cultivation medium. Processing of livestock waste with earthworms can produce high economic value cocoon and biomass. To find out the differences in cocoon and biomass production in five types of livestock waste, a research was carried out using a Completely Randomized Design with five treatments and five replications. The results showed that the use of feces of cattle, goats, horses, broiler chickens, and rumen contents as the medium of Eisenia foetida cultivation had a significant effect (P<0.05) on cocoon and biomass production. Duncan's test results showed that the highest cocoon production of 123.0 eggs/nest box obtained on goat feces medium was significantly different (P<0.05) with feces of cattle, horses, chickens and rumen contents. The highest production of earthworm biomass of 1339.0 eggs/nest box obtained in horse feces medium was significantly different (P<0.05) with feces of cattle, goats, chickens, and rumen contents. The conclusion is: 1) to produce the most cocoon using goat feces; 2) to produce the most earthworm biomass using horse feces; 3) to produce the highest weight gain of earthworms using cattle feces; 4) to produce a weight size per head of earthworms using high rumen contents; and 5) the use of feces of broiler chickens is not recommended as a whole (100%) as a medium or feed in livestock waste treatment because it causes all earthworms to die, so they need to be mixed with other medium or feed ingredients.